2006
DOI: 10.4314/ajpsy.v9i1.30205
|View full text |Cite
|
Sign up to set email alerts
|

The conceptualisation of "soft skills" among medical students before and after curriculum reform

Abstract: Objective: This paper reports on the conceptualisation of "soft skills" as part of a study carried out among two groups of undergraduate medical students before and after curriculum reform at the School of Medicine of the University of Pretoria. Congruent with a call from the World Psychiatric Association, the curriculum reform that was undertaken aimed, inter alia, to place more emphasis on soft skills, including professional interpersonal and social skills, communication skills, and professional and ethical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…The results were mixed, with one study in western Nepal showing an association between positive attitude scores and prior completion of a communication skills curriculum, whereas a similar study in Sri Lanka found no significant association . A South African study demonstrated that longitudinal curricular reform focused on the teaching of interpersonal, social and communication skills led to a more mature and practical understanding of communication skills in the workplace . We were unable to identify any studies that evaluated communication between health care providers involved in team‐based care in a LMIC context.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The results were mixed, with one study in western Nepal showing an association between positive attitude scores and prior completion of a communication skills curriculum, whereas a similar study in Sri Lanka found no significant association . A South African study demonstrated that longitudinal curricular reform focused on the teaching of interpersonal, social and communication skills led to a more mature and practical understanding of communication skills in the workplace . We were unable to identify any studies that evaluated communication between health care providers involved in team‐based care in a LMIC context.…”
Section: Resultsmentioning
confidence: 89%
“…There were no context‐specific assessment or educational tools for NTS of providers in LMICs identified in this review. However, five studies described other training or assessment efforts that incorporated individual elements of NTS . Researchers in Tanzania and Guyana reported on their experience performing trauma team training (TTT) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The views on their development of soft skills differed very little between the traditional and reformed curriculum groups, except for students from the reformed curriculum seeming 'more prepared, and [feeling] that teaching and training efforts left then well-equipped with soft skills'. 7 Further consideration needs to be given to the intention of a changed curriculum compared to the real effect. In this regard, the following comment by Coulehan may be relevant: '… in an attempt to render professionalism more quantifiable, it may use skills and practices as surrogates for virtue.'…”
Section: Discussionmentioning
confidence: 99%
“…This present study results are also in line with the above study. Van Staden CW mentioned that, teaching soft skills as «Golden Threads" for the undergraduates to achieve competencies towards inter personal skills and professional, ethical attitudes (Table 11) [20]. Depicts the attitude of dental personnel towards training of communicative skills which will improve dentist's ability to communicate with the patients easily.…”
Section: Discussionmentioning
confidence: 99%